2009
DOI: 10.1002/stem.238
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Thymic Epithelial Cell Progenitors by Mouse Embryonic Stem Cells

Abstract: Thymopoiesisis regulated by the thymic microenvironment, of which epithelial cells are the major components. Both cortical and medullary thymic epithelial cells (TECs) have been shown to arise from a common progenitor cell. Here we show for the first time that mouse embryonic stem cells (mESCs) can be selectively induced in vitro to differentiate into cells that have the phenotype of thymic epithelial progenitors (TEPs). When placed in vivo, these mESC-derived TEPs self-renew, develop into TECs, and reconstitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 59 publications
4
79
0
Order By: Relevance
“…In controls, transplantation of CD4 -CD8 -CD45 + immature thymocytes and/or mESC-derived EpCAM1 -cells could not form normal thymic architecture in vivo. Further analysis showed that all stages of T cells were generated in the EpCAM1 + , but not in the EpCAM1 -cell grafts (Lai & Jin, 2009). These data suggest that the mESC-derived EpCAM1 + cells can form normal thymic architecture that supports T-cell development in vivo.…”
Section: Generation Of Thymic Epithelial Progenitors From Mouse Embrymentioning
confidence: 80%
See 4 more Smart Citations
“…In controls, transplantation of CD4 -CD8 -CD45 + immature thymocytes and/or mESC-derived EpCAM1 -cells could not form normal thymic architecture in vivo. Further analysis showed that all stages of T cells were generated in the EpCAM1 + , but not in the EpCAM1 -cell grafts (Lai & Jin, 2009). These data suggest that the mESC-derived EpCAM1 + cells can form normal thymic architecture that supports T-cell development in vivo.…”
Section: Generation Of Thymic Epithelial Progenitors From Mouse Embrymentioning
confidence: 80%
“…We have investigated whether mouse ESCs can be selectively induced to generate TEPs in vitro. By using both threedimension embryoid body formation and two-dimension monolayer culture systems in the presence of four growth factors [fibroblast growth factor (FGF)-7, FGF-10, bone morphogenetic protein 4 and epithelial growth factor], we have shown for the first time, that murine ESCs (mESCs) can be selectively induced to differentiate into TEPs (Lai & Jin, 2009). Under these culture conditions, EpCAM1+ cells can be generated from mESCs (Lai & Jin, 2009).…”
Section: Generation Of Thymic Epithelial Progenitors From Mouse Embrymentioning
confidence: 99%
See 3 more Smart Citations